Gender in urban food systems - Halliday, Jess; Joshi, Deepa; Young, Laine; Veenhuizen, René van (2020)
It’s no secret that the food system has an endemic gender problem. There are significant barriers to participation in food value chains due to socially determined identities, roles, rights and obligations of women and men, and structural inequalities embedded in the system.